2022
DOI: 10.1097/ijg.0000000000001980
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Surgical Interventions in Primary Congenital Glaucoma Patients

Abstract: Purpose: The aim was to report long-term surgical success of primary congenital glaucoma (PCG) patients in Thailand. Materials and Methods: PCG patients who underwent one of the following primary operations: trabeculotomy, goniotomy, trabeculectomy, combined trabeculotrabeculectomy (CTT) and diode transscleral cyclophotocoagulation (TSCPC) between January 1992 and January 2018 were reviewed. Surgical success was defined as intraocular pressure (IOP) between 5 and 21 mm Hg with or without antiglaucoma medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A recent report from Thailand assessed the long-term surgical success of various techniques in PCG. In this study, Suvannachart et al 22 concluded that primary trabeculotomy and primary CTT had the highest long-term success rates in PCG patients (81 eyes from 55 PCG patients, 5-year follow-up). Except for the pending results of a multicenter randomized controlled trial conducted by Fang et al, 29 we are unaware of any published studies comparing long-term results of CTT compared with trabeculotomy in the same target population with PCG…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…A recent report from Thailand assessed the long-term surgical success of various techniques in PCG. In this study, Suvannachart et al 22 concluded that primary trabeculotomy and primary CTT had the highest long-term success rates in PCG patients (81 eyes from 55 PCG patients, 5-year follow-up). Except for the pending results of a multicenter randomized controlled trial conducted by Fang et al, 29 we are unaware of any published studies comparing long-term results of CTT compared with trabeculotomy in the same target population with PCG…”
Section: Discussionmentioning
confidence: 62%
“…4,6,[12][13][14][15][16][17][18][19][20][21] In Thailand, a recent study comparing various techniques including trabeculotomy, goniotomy, trabeculectomy, and CTT concluded that primary trabeculotomy and primary CTT had the highest long-term success rates in PCG patients. 22 As the optimum first-line approach is still the subject of considerable debate in Tunisia and North African countries, we conducted this study to assess 10-year outcomes as well as factors influencing the surgical success of CTT in children with PCG in a North African pediatric population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 ] and Suvannachart et al . [ 29 ] in their study. We prefer not to use MMC during the primary procedure due to the risk of hypotony in the early postoperative period and bleb related complications in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] and 79.4% reported by Suvannachart et al . [ 29 ] The probable reason for the high success rate could be the use of MMC by Zhang et al . [ 28 ] and Suvannachart et al .…”
Section: Discussionmentioning
confidence: 99%